Developments in surface contamination and cleaning. Vol. 4, - Kohli, Rajiv, 1947- (William Andrew ; Elsevier Science [distributor], 2011)
In this series Rajiv Kohli and Kash Mittal have brought together the work of experts from different industry sectors and backgrounds to provide a state-of-the-art survey and best-practice guidance for scientists and engineers engaged in surface cleaning or handling the consequences of surface contamination. The expert contributions in this volume cover important fundamental aspects of surface contamination that are key to understanding the behavior of specific types of contaminants. This understanding is essential to develop preventative and mitigation methods for contamination control. The coverage complements the treatment of surface contamination in vol.1, Fundamental and Applied Aspects. This volume covers: Sources and Generation of Particles; Manipulation Techniques for Particles on Surfaces; Particle Deposition and Rebound; Particle Behavior in Liquid Systems; Biological and Metallic Contamination; and includes a comprehensive list of current standards and resources. Feature: Comprehensive coverage of innovations in surface contamination and cleaning Benefit: One-stop series where a wide range of readers will be sure to find a solution to their cleaning problem, saving the time involved in consulting a range of disparate sources. Feature: Written by established experts in the contamination and cleaning field Benefit: Provides an authoritative resource Feature: Each chapter is a comprehensive review of the state of the art. Benefit: Can be relied on to provide insight, clarity and real expertise on up-to-the-minute innovations. Feature: Case studies included Benefit: Case studies help the reader see theory applied to the solution of real-world practical cleaning and contamination problems.
Keywords: Surfaces (Technology); Surface contamination -- Prevention.; Particles -- Measurement.; Cleaning.; Coatings.; Dust control.; elektronické knihy; electronic books